International arbitral institutions - Syed Jaafar, Syed Hamid Albar; Eishan Jan, Mohammad Naqib; Ahmad, Muhamad Hassan (CLJ Publication, 2020)
This chapter generally discusses international arbitration and tribunals, the key term here is ‘international arbitration’. What does it mean? How does it work in practice? Can it contribute to the creation of a peaceful world through settlement of disputes between states and non-state actors? These are some of the main issues that this chapter seeks to explore. The main international arbitration body which this chapter refers to is the Permanent Court of Arbitration (‘PCA’). Over the past decades, the use of international arbitration has grown remarkably, mainly in Asia and Africa. The emergence of new arbitration centres is one of the salient features of this growth which has contributed tremendously to the development of institutional arbitration. Only 10% of the current institutions existed before 1940. In the last 30 years, 70% of the arbitration institutions have been established — 50% and 20% in the last 20 and 10 years respectively. Even though there is a slow growth rate at the moment — in 2008, 2009, 2010, at least two new institutions were created in each year. International arbitration is one of the most important legal means of settling international disputes alongside judicial settlement. In addition to these, there are diplomatic means of settling international disputes but they fall outside the scope of this chapter. This chapter focuses on ‘international arbitration courts and tribunals’ which, like judicial settlement, is a legal means. Unlike judicial settlement, which is characterised by the fact that a dispute is settled by a standing tribunal (like the International Court of Justice (‘ICJ’)), arbitration is designed by the parties to the disputes. They can choose the arbitrators, the law governing arbitration proceedings (the procedural law) and the law applicable to the dispute (the applicable law). International arbitration can take place between two or more disputing parties. It can take place between two states (interstate arbitration); between states and non-state actors; individuals or private companies (sometimes termed ‘mixed arbitration’); or between two non-state actors. Irrespective of the status of the disputants, arbitration can be conducted on ad hoc basis, in which case the parties to the dispute are responsible for determining and agreeing on the arbitration procedure, not subjected to the procedures of an arbitral institution; or it can be conducted by institutional arbitration. In institutional arbitration, the parties rely on the procedural rules of a chosen arbitration tribunal, and are assisted during the procedure by that tribunal. There are many different arbitration courts and tribunals that can assist in the settlement of international disputes. The most prominent among them include the PCA in the Hague and the International Centre for the Settlement of Investment Disputes (‘ICSID’) in Washington, which settles investment disputes between the state and a foreign investor. The subject matter of international disputes that can be settled through international arbitration includes commercial law disputes between two private parties, investment disputes between states and foreign investors, or disputes between states in relation to the law of the sea, for instance, boundary determination. This chapter focuses mainly on arbitration involving at least one state; and disputes in the field of public international law rather than private international law.